FREEDOM OF EXPRESSION AND CENSORSHIP IN PERFORMING ARTS: A LEGAL AND ETHICAL PERSPECTIVE - Bishnoi, Narender Kumar; Chaudhary, Paras (ShodhKosh: Journal of Visual and Performing Arts, 2024)
With an emphasis on the ethical and legal factors that impact creative freedom, this study investigates the intricate relationship between free speech and censorship in the performing arts. In light of the importance of the performing arts as a platform for social criticism and cultural reflection, this research investigates the legal safeguards that artists have, especially in democracies like India. Censorship systems, which aim to maintain public order, moral principles, and cultural sensitivity, often moderate these liberties. Courts' interpretations of the limits of speech in the performing arts are examined in this article via an examination of seminal judgments from India and other countries. It also takes into account the social effects of censorship on innovation, creativity, and public debate as well as the ethical considerations of limiting art. This paper proposes legislative changes to better balance creative freedom with community norms by comparing censorship regulations across countries. In the end, the piece argues for a balanced approach that safeguards creative expression while upholding ethical limits, with the goal of creating a democratic setting where the performing arts may flourish as catalysts for social transformation.